Bermuda grass pollen allergen implicated in clinically relevant cross‐reactivity to multiple grains: A case report. Issue 1 (21st January 2019) - Lee, Jihye; Kang, Young Joong
Abstract: Background: Anaphylaxis is a severe and potentially fatal type of allergic reaction and is characterized by the rapid development of symptoms in the respiratory and circulatory systems, possibly leading to death if not treated properly. Occupational anaphylaxis, which does not exhibit significant differences in pathogenesis from the nonoccupational form, develops in response to work‐related triggers. However, the onset of occupational anaphylaxis can also be triggered by other factors. Therefore, an unexpected episode may occur due to exposure to a previously sensitized antigen or cross‐reaction in the occupational environment, even if the direct trigger has been removed. Accordingly, it is difficult to diagnosis and treat such cases and ensure avoidance of potential triggers. Case presentation: An adult male patient developed anaphylaxis following exposure to grass antigens while replacing and burying sewer pipes at a theme park. He later developed cross‐reactivity to other grains. Despite symptomatic treatment, his total serum level of allergen‐specific immunoglobulin E (Ig E) antibodies continuously increased, and thus, he was admitted with severe hypersensitivity, at which time his serum levels of Ig E antibodies specific for Bermuda grass, wheat, and rice had also increased. Conclusion: In Korea, Bermuda grass is rarely seen and is generally found in athletic fields or theme parks. Following exposure to this relatively rare grass, our patient exhibited new anaphylactic responses to various external antigens. Therefore, we attribute his severe anaphylaxis to sensitization caused by Bermuda grass exposure and cross‐reactive hypersensitivity to other grains.